Dietary canolol induces apoptosis in human cervical carcinoma HeLa cells through ROS-MAPK mediated mitochondrial signaling pathway: In vitro and in vivo. (25th February 2019) - Xia, Xiaoyang; Xiang, Xia; Huang, Fenghong; Zheng, Mingming; Zhang, Zhen; Han, Ling
Abstract: Canolol (4-vinylsyringol), extracted form crude canola oil, is the promising drug toward cancer prevention and treatment. The current studies focus on the role of COX-2 signaling pathway in canolol-induced apoptosis in cancer cells. It is still unknown whether mitochondria and MAPK signaling pathways are involved. To elucidate the roles of above signaling pathways in canolol-induced apoptosis in cancer cells, human cervical carcinoma cell line HeLa and HeLa xenograft tumor model are adopted. Canolol induced apoptosis of HeLa cells and inhibited tumor growth with low systemic adverse effect, accompanying with excess generation of intracellular ROS and lysosome rupture. The results in vitro and in vivo confirmed that MAPK signaling pathways mediated mitochondrial signaling pathway activation were involved in canolol-induced apoptosis. In conclusion, these data showed that canolol induced apoptosis in HeLa cells through ROS-MAPK mediated mitochondrial signaling pathway, providing a view of the potential application of canolol as an anticancer agent. Highlights: Canolol inhibited cell survival and induced apoptosis in HeLa cells. Canolol activated MAPK and mitochondrial signaling pathways in HeLa cells. Canolol had less cytotoxicity in vitro and low systemic adverse effect in vivo .